Tests for a Systematic Risk Component in Deviations from Uncovered Interest Rate Parity - McCurdy, Thomas H.; Morgan, Ieuan G. (Review of Economic Studies, 1991)
In the intertemporal asset pricing model, investments in spot foreign currencies involve time-varying risk proportional to the conditional covariance of the value of the position with the intertemporal marginal rate of substitution of domestic currency. We detect such risk premia in deviations from uncovered interest rate parity using weekly spot currency prices and Eurocurrency interest rates. Our tests use the conditional capital asset pricing model with a world equity index as benchmark to represent aggregate wealth.